(untitled) (Journal of history, 2020)
This article discusses the political program of the party, who opposed the imperial government, as well as the activities and goals of representa- tives of the national intelligentsia and the formation of the ideas of national statehood in the activities of the Alash movement. The main purpose of this study is a deep analysis of the representatives of the national intelli- gentsia in the formation of statehood and the revival of the national ideol- ogy. The article also examines the role of representatives of the national intelligentsia in the revival of the national idea and national associations.